PENGEMBANGAN MODUL INTERAKTIF KOMPUTER DAN JARINGAN DASAR BERBASIS ANDROID - Saza Kurnia Utami; Dony Novaliendry (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
The use of technology in education can simplify the learning process and increase the potential of students in developing interests and potential so that learning objectives can be achieved. Based on observations on the Computer and Basic Networking subjects at SMKN 5 Padang that teachers have not implemented the media in the form of interactive modules in the learning process so that it has an impact on student learning outcomes. The purpose of this research is to develop an interactive module Computer and Basic Networks. Making this module using Android Studio software. The development method begins with system analysis (Fishbone diagram), analysis of the current system, and analysis of the proposed new system in the form of use cases, activity diagrams, and interface design. The conclusion of the development of this module is to produce an interactive module application Computer and Basic Networks that can be accessed via an android smartphone. In addition this module can also be run on a computer / PC. With the media in the form of interactive modules, it can be easier for students to understand the material and is very practical to be used as a learning medium. Keywords:Interactive Modules, Computers and Basic Networks, Android Studio